Learning Design Education Religion Islam In School - Nurdalia (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
Structure content learning without considering learning models or methods so that the information presented by the teacher is forgotten quickly. The object of the paper: This article examines the procedures for planning, defining, and creating an organizing strategy for subject-matter learning in the context of professional Islamic religious education. Temporary, as in the theory applied to the issue This design model theory learning is in reference to the Kemp, Dick, and Carey approach system as well as the Dageng model. All three address the formation of learning strategies, the development of process measurement learning, and analysis condition learning. Inductive reasoning, descriptive-analytical thinking, and characteristic libraries are all topics covered in this essay. The analysis of data from characteristic facts, facts specific to directions, and general information about design development in Islamic religious education learning form the basis of the debate. Review the report of outcomes. This demonstrates that: (1) Kemp's model may be used to construct Islamic religious education based on the four planning learning elements of participant students, objectives, methods, and evaluation. Dick and Carey's term